CoreTIA: a modular, statistically robust transduction inhibition assay for AAV neutralization - Kovács, Beatrix; Somogyi, Fanni; Szabó, Viktória; Nagy, Zoltán Zsolt; Hernádi, István; Mátyás, Ferenc; Vanduffel, Wim; Szemlaky, Zsuzsanna; Rózsa, Balázs; Ulbert, István; Hillier, Dániel (Frontiers in Immunology, 2025)
Adeno-associated virus (AAV) gene therapy is often limited by pre-existing neutralizing antibodies (NAbs), yet current assays for NAb detection lack standardization and rarely quantify uncertainty, complicating cross-study comparisons. We present coreTIA (core Transduction Inhibition Assay), a comprehensive framework providing a modular experimental protocol and a statistically robust analysis pipeline. This integrated method delivers precise, reproducible NAb titers with quantified uncertainty for every result. coreTIA’s statistical framework enables robust estimation of neutralization even when dilution series are incomplete, helping to reduce repeat testing and minimizing sample volume requirements. Evaluation and refinement of key assay parameters support consistent performance across AAV serotypes. By providing a protocol and analysis suite as an open resource, coreTIA facilitates more consistent and transparent NAb measurement, potentially aiding assay harmonization and regulatory assessment, addressing a key barrier to progress in gene therapy research and development.